Relationship Between the Business Cycle Indicator and Taiwan Stock Market Performance - Chen, Po-Chung; Brůna, Karel, 1973-; Šímová, Kateřina; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2025)
This study examines the usefulness of using Taiwan's Business Cycle Indicator (BCI) to make investment decisions in the 0050 ETF, which is a proxy for the TAIEX. It examines the link between BCI and the TAIEX monthly average growth rate by employing the ARDL model and Granger causality tests. However, the results show that there is a statistically significant long-run relationship and bidirectional short-run causality with a relatively small impact magnitude. To enrich the econometric analysis, the study compares the investment performance of five strategies: Lump-Sum, Dollar-Cost Averaging, BCI-based, RSI, and MACD using R simulations. Among these, the BCI-based strategy shows better long-term risk-adjusted performance. These results indicate that although BCI may not have strong predictive power in the short run, it can still improve long-term investment timing when incorporated into strategy design.
Vedoucí práce: Karel Brůna
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: finance and accounting [obor dipl. práce]; diplomové práce; master's theses